Korupsi dalam Telaah Ayat Ahkam dan Hukum Positif Nasional - Edyar, Busman; Hayati, Ilda; Saputra, Kevin (AL QUDS : Jurnal Studi Alquran dan Hadis, 2024)
This research aims to explain the perspective of legal verses in the Qur'an and national positive law against corruption. The type of research is normative juridical with a comparative approach between Islamic law and national positive law which is analyzed using prescriptive analysis. The results of the research show that the Qur'an and national positive law have the same perspective on corruption as a prohibited position-related act. There are several derivations used in the Qur'an that have a connection with corrupt practices, for example ghulul (fraudulent acts), sirqah (theft), betrayal, risywah (bribery), and even hirabah (destroyer of order). According to positive law, corruption is an act against the law with the intention of enriching oneself, others, or which results in harm to the state or the country's economy.